1995
DOI: 10.1088/0953-4075/28/17/019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a laser pulse photoionizing an effectively excited three-level atom on the ion yield

Abstract: The population inversion in a three-level atomic system, interacting with two coherent laser pulses, occurs from the first level to the third level at the optimal detunings of the laser frequencies near the two-photon resonance. An examination is performed to see whether the energy density and time-delay of the photoionizing laser can significantly influence the ion yield for the case where the atom interacts with two coherent pulses and one photoionizing pulse incoherently coupled. The well-known three-colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The atomic-level populations, which are calculated by using U, = Uz = 5 J m-' for quasi-monochromatic pulses, are presented in figure 4. It is found that the laser bandwidth causes the radiation-atom interaction to be incoherent, as shown in ourprevjous calculation (Choe et al 1995). That is, it is believed that the effect of laser bandwidth causes significantly different behaviours of atomic-level populations due to the overcoming of the Rabi splitting and the reduction of the Rabi oscillation, compared with the results for a situation of monochromatic radiation sources.…”
Section: Population Dynamics In the Thin Mediumsupporting
confidence: 64%
“…The atomic-level populations, which are calculated by using U, = Uz = 5 J m-' for quasi-monochromatic pulses, are presented in figure 4. It is found that the laser bandwidth causes the radiation-atom interaction to be incoherent, as shown in ourprevjous calculation (Choe et al 1995). That is, it is believed that the effect of laser bandwidth causes significantly different behaviours of atomic-level populations due to the overcoming of the Rabi splitting and the reduction of the Rabi oscillation, compared with the results for a situation of monochromatic radiation sources.…”
Section: Population Dynamics In the Thin Mediumsupporting
confidence: 64%
“…One of the reasons for the utilization of such a scheme is that the spectroscopic parameters (Krynetskii et al 1991), lifetimes of the excited states (Krynetskii et al 1991, Blagoev and Komarovskii 1994, Bowers et al 1996, dipole moments of the transitions (Burshtein et al 1974) and energy levels (Martin 1978) have been thoroughly studied. The isotope shifts of all the Yb isotopes and hyperfine structure (hfs) constants of the odd isotopes have been accurately measured for the 4f 14 6s 2 1 S 0 -4f 14 6s6p 3 P o 1 (555.648 nm) transition by several groups (Broadhurst et al 1974, Clark et al 1979, Jin et al 1991, van Wijngaarden and Li 1994 and for the 4f 14 6s6p 3 P o 1 -4f 13 6s 2 6p ( 7 2 , 3 2 ) 2 (581.027 nm) transition by Choe et al (1995a) and Borisov et al (1996). The limitation of this photoionization scheme is that the isotopic selectivities that can be obtained for the 4f 14 6s 2 1 S 0 -4f 14 6s6p 3 P o 1 (555.648 nm) transition are rather small.…”
Section: Introductionmentioning
confidence: 98%
“…Isotope-selective excitation/ionization using laser atomic beam spectroscopy (Letokhov 1987) has become a potential tool for studying the laser isotope separation processes. There has been genuine interest for studying the isotopic selectivities of lanthanides such as Gd (Santala et al 1994, Suryanarayana and, Yb (Choe et al 1995a, Borisov et al 1996 and La Shaw 1995, Sankari and because of their economic value. Diode-laser initiated resonance ionization mass spectrometry has been used (Shaw et al 1989) for isotope-selective studies of low-abundant 138 La isotope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fixed detunings, if a slightly incomplete inversion is allowed, will allow an easier experimental approach. In previous studies, the optimal detunings for the different Rabi frequencies could only be determined numerically, based on the formulae of the optimal detunings in the case of square pulses (Choe et al 1995). Therefore, the main purpose of our study is to suggest a method to obtain constant optimal detunings which cause optimal inversion in the case of different Rabi frequencies and present some values of the optimal detunings found by using the optimal detuning parameter.…”
Section: Introductionmentioning
confidence: 99%